The effect of hyperlipidemia on bone graft regeneration of peri-implantal created defects in rabbits - Mehmet Bugrul Tekin; Hulya Toker (SpringerOpen, 2019)
Abstract Aim It is reported that hyperlipidemia affects quality and density of bone and adversely affects wound healing. The effect of hyperlipidemia on implant osseointegration and peri-implant defect regeneration has not been fully explained. The purpose of this study was to examine the effects of hyperlipidemia on the healing potential of the materials used for peri-implant bone regeneration and implant stability. Materials and methods Twelve male, New Zealand rabbits were used in this study. Half of the rabbits were fed a 2% cholesterol diet for 8 weeks to induce hypercholesterolemia. Peri-implant defects (7 mm diameter) were created in the tibias of rabbits and placed implants (3.3 mm in diameter). This study was conducted as a split-mouth design. Animals were randomly divided into two groups: (1) hypercholesterol+autogenous graft group and hypercholesterol+xenograft group (n = 6), and (2) autogenous graft and xenograft groups as controls (n = 6). At 8 weeks after surgery, the rabbits were euthanized. During implant surgery and at 8 weeks, implant stability was measured with resonance frequency analysis (RFA values). Bone-to-implant contact (BIC) was analyzed via histomorphometric analysis. Results Hyperlipidemic groups showed significantly lower BIC values than those of the control groups at 8 weeks (p < 0.05). According to baseline RFA readings, there was no significant difference between control and hyperlipidemic groups (p ˃ 0.05). The hypercholesterol+autogenous graft group had significantly lower RFA readings and BIC values than the hypercholesterol+xenograft group at 8 weeks (p < 0.05). Conclusion Within the limitations of this study, it was found that hyperlipidemia may negatively affect the implant stability especially in the autogenous group and also, may decrease peri-implant bone regeneration. However, further studies are necessary to confirm these results more.